Adoption of Artificial Intelligence (AI) Technology in Enhancing Tourist Experience: A Conceptual Model - Andrianto, Tomy; Tangit, Tania Maria; Minh, Nguyen Cong (Integrasi Sains Media, 2025)
The rapid advancement of Artificial Intelligence (AI) technologies is fundamentally transforming the global tourism industry, reshaping how travellers plan, experience, and reflect on their journeys. AI applications such as chatbots, virtual assistants, intelligent recommendation systems, and real-time translation tools have enhanced personalization, operational efficiency, and real-time decision-making throughout the tourist experience. However, despite AI’s potential to drive innovation and competitiveness, its adoption faces critical barriers, including data privacy concerns, algorithmic bias, digital literacy gaps, and unequal technological infrastructure. This study explores AI adoption's drivers, barriers, and strategic implications in tourism through a qualitative expert panel discussion involving academics, industry practitioners, and government representatives. Data were collected via a structured email-based discussion guide covering AI applications, operational benefits, motivational factors, adoption challenges, ethical considerations, and future directions. Findings reveal that AI enhances tourist experiences and business operations by enabling hyper-personalization, improving resource optimization, and supporting sustainable tourism governance. Ethical and regulatory challenges remain significant, particularly around trust, transparency, and data protection. The study proposes a conceptual model that positions AI as a transformative enabler, moderated by governance frameworks and ethical considerations. This research offers strategic insights for policymakers, industry stakeholders, and scholars, emphasizing the need for inclusive digital infrastructure, ethical AI design, and sector-specific regulations to ensure responsible, equitable, and sustainable AI adoption in the tourism sector.